2006
DOI: 10.1073/pnas.0511315103
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent ligation of the B cell receptor induces receptor activation but fails to promote antigen presentation

Abstract: We explored the role of antigen valency in B cell receptor (BCR) activation and rearrangement of intracellular MHC class II compartments as factors that contribute to the efficacy of antigen presentation. Using primary B cells that express a hen egg lysozyme (HEL)-specific BCR, we found that oligomeric HEL more efficiently promoted both BCR activation and internalization than did monovalent HEL, although monovalent HEL, unlike monovalent Fab fragments of anti-Ig, readily triggered the BCR. Nonetheless, oligova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 28 publications
7
122
0
Order By: Relevance
“…The p62 UBA precipitates and WCLs were then probed for BCR IgM heavy chain ( Figure 1A, anti-IgM). The results demonstrate the presence of 2 different molecular weight forms of IgM heavy chain in the WCLs (which we [J.R.D., unpublished results, August 2006] and others 27 have determined represent different glycoforms of the IgM heavy chain) and show that the p62 UBA ubiquitin-binding protein selectively binds to the lower molecular weight heavy chain glycoform.…”
Section: Resultsmentioning
confidence: 89%
“…The p62 UBA precipitates and WCLs were then probed for BCR IgM heavy chain ( Figure 1A, anti-IgM). The results demonstrate the presence of 2 different molecular weight forms of IgM heavy chain in the WCLs (which we [J.R.D., unpublished results, August 2006] and others 27 have determined represent different glycoforms of the IgM heavy chain) and show that the p62 UBA ubiquitin-binding protein selectively binds to the lower molecular weight heavy chain glycoform.…”
Section: Resultsmentioning
confidence: 89%
“…The initiation of B cell activation has been shown to be sensitive to each type of these Ag presentation formats. For example, early studies extensively investigated how Ag valency can affect B cell activation (10)(11)(12) and the subsequent Ab responses (6)(7)(8). It is generally observed that multivalent Ags with high valency are more potent in inducing Ab responses as compared with monovalent Ags with low valency.…”
mentioning
confidence: 99%
“…In the IgHEL tg system, stimulation with soluble HEL is not sufficient to induce vigorous proliferation in vitro, perhaps reflecting the reduced valency of monovalent HEL or a less mature developmental status as reflected by high levels of surface IgM (16,22). Interestingly, Itpkb-deficient cells failed to proliferate in response to HEL to the extent observed in WT IgHEL tg B cells (Fig.…”
Section: Itpkb-deficient B Cells Are Anergicmentioning
confidence: 97%